Functional characterisation of the hypertrehalosaemic hormone from the Indian stick insect Carausius morosus: metabolic and myotropic studies - Katali, Ottilie Kandiwapa Hasiike (Department of Biological Sciences, 2017)
Neuropeptides of the adipokinetic hormone/red pigment concentrating hormone (AKH/RPCH) family are well known as regulators for many physiological processes in insects, notably energy metabolism, and a possible role in myostimulation. The Indian stick insect Carausius morosus contains two members of this family, hypertrehalosaemic hormone I and II (Carmo-HrTH-I and -II). Both these are decapeptides and they differ only at position 8, where the tryptophan of Carmo-HrTH-I is C‐mannosylated. It is known that Carmo-HrTHs increase the carbohydrate (trehalose) concentration in the haemolymph via a G protein-coupled receptor. The current study seeks to identify which part of the HrTH amino acid sequence is necessary to interact with the receptor on the fat body of C. morosus to trigger a response (hypertrehalosaemia) eventually leading to the release of carbohydrates into the haemolymph. In addition, the role of Carmo-HrTHs in stimulating the heart rate through myostimulation was also investigated. Two biological assays were used to assess the potencies of various analogues, in comparison to that of the native peptides: (1) the carbohydrate-mobilizing assay assessed the increase in levels of carbohydrates; and (2) the semi-exposed heart assay assessed the increase in heart rates. The current study confirmed that both Carmo-HrTH-I and -II are capable of increasing the haemolymph carbohydrates in ligated stick insects. The results of the current study revealed, for the first time, that these peptides also similarly stimulate the heart rate of the stick insect. Thus, Carmo-HrTH-II was used as a lead peptide in the current study on which various naturally-occurring AKH peptides and systematically altered analogues were based. The selected naturally-occurring AKH peptides had a single or double amino acids replacement in comparison to Carmo-HrTH-II and some were octapeptides. Each systematically altered analogue of the native Carausius HrTH II had a single amino acid replaced with alanine. Additionally, two analogues that lacked the N-terminal pyroglutamate residue or had a free threonine acid at the C-terminus instead of an amide were also tested. The results showed that the N- or C- terminal modified analogues have no hypertrehalosaemic activity in C. morosus and are also incapable of increasing the heart rate of this insect as high as Carmo-HrTH-II. This suggests that the blocked termini are important features, for both peptide protection and receptor binding. The structural requirements of C. morosus receptor(s) for Carmo-HrTHs appear to be very specific. The receptor(s) do not accept octapeptides and only four out of the fourteen decapeptides elicited at least 46% of the biological activity as compared to the native peptide and the rest (ten) were not active. This implies that the HrTHs receptor (s) for C. morosus do not tolerate the replacement of most single amino acids. In the heart assay, known cardio-stimulatory peptides were applied to the semi-exposed heart of C. morosus to establish the potential extent of cardioexcitation. The results of this study revealed that crustacean cardioactive peptide and proctolin are capable of increasing the heart beat rate of the stick insect more than the AKH/RPCH peptides. It was also shown that the stick insect heart beat rate can be inhibited by octopamine. This is the first study to investigate, in detail, the importance of structural features of the hypertrehalosaemic hormones of the Phasmatodea insects, and is therefore an important contribution to designing environmentally friendly insect-specific pesticides.